2015
DOI: 10.1177/0363546515598995
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport After Rotator Cuff Tear Repair

Abstract: Most recreational athletes return to sports at the same level of play as before their injury, but only half of professional and competitive athletes return to an equivalent level of play.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 36 publications
(42 reference statements)
3
87
1
2
Order By: Relevance
“…However, only 5 climbers (42%) had regained their previous climbing level at re-evaluation ( Figure). Our data are in line with a recent meta-analysis from Klouche et al 14 on the sports-specific outcome after surgical therapy of rotator cuff pathologies in overhead athletes. The authors analyzed the outcome in 859 overhead athletes (874 shoulders), such as baseball players, golfers, and tennis players, with a mean age of 42.6 years and an acute onset of rotator cuff pathology in 62% of the cases.…”
Section: Discussionsupporting
confidence: 92%
“…However, only 5 climbers (42%) had regained their previous climbing level at re-evaluation ( Figure). Our data are in line with a recent meta-analysis from Klouche et al 14 on the sports-specific outcome after surgical therapy of rotator cuff pathologies in overhead athletes. The authors analyzed the outcome in 859 overhead athletes (874 shoulders), such as baseball players, golfers, and tennis players, with a mean age of 42.6 years and an acute onset of rotator cuff pathology in 62% of the cases.…”
Section: Discussionsupporting
confidence: 92%
“…However, conservative treatment might require long-term therapy and during that period the athlete will be forced to take a long-term break from the sport. The overall rate of return to sports after rotator cuff repair was 84.7%, including 66.9% at an equivalent level of play, 4 to 17 months after surgery [24]. In this study, 22 patients had no shoulder pain at final follow-up, and the rate of return to sports after rotator cuff repair was 88% at final follow-up.…”
Section: Discussionmentioning
confidence: 73%
“…These patients are especially at risk, in particular those who practice overhead and contact sports. 25 In a recent meta-analysis, Klouche et al 13 showed that the overall rate of return to sports after repair of rotator cuff tears was 84.7%, with 65.9% of participants returning to play at the same level between 4 and 17 months after surgery. In our study, 95.8% of patients were able to return to sports, and 91.3% were able to return to the same level.…”
Section: Discussionmentioning
confidence: 99%